Langerhans cell histiocytosis of the left tibia bone: A case report (Indian Journal of Case Reports, 2021)
Langerhans cell histiocytosis (LCH) is a rare group of disorders including single lesion to widespread disseminated disease. The incidence of this disorder is around 5–6 cases per million children per year with more than 50% of cases are diagnosed between 1 and 15 years old and peaks between 1 and 4 years old. This case report describes a rare case of a 2-year-old boy patient with a single lesion LCH in the left tibia. The diagnosis was challenging as the presenting symptom was not specific and the radiograph examination mimicked osteomyelitis. The diagnosis was then confirmed with immunohistochemistry (IHC) S-100 staining. The patient had a surgical curettage, application of bone graft and plate, and screw fixation. At 9 months follow-up, the patient was able to walk without gait disturbance and there was no new lesion reported. This case report pointed out that in the diagnosis of LCH, physical, and radiological examination mimicked other more common diseases and IHC S-100 staining had confirmed the diagnosis of LCH. It also showed that for a small single lesion of LCH, minimal intervention leads to a good outcome.